Social entrepreneurship : a modern approach to social value creation - Brooks, Arthur C. (Upper Saddle River, New Jersey : Pearson/ Prentice Hall, 2009)
Social entrepreneurship : a modern approach to social value creation seeks to bring together the established pedagogy of entrepreneurship, as taught in today's best management schools, with cutting edge nonprofit and public management tools. This book is intended as a primary text for the growing list of courses offered in social entrepreneurship or as a secondary resource for courses in nonprofit management, nonprofit leadership, or commercial entrepreneurship.
Chapter 1: An introduction to social entrepreneurship -- Chapter 2: Ideas and opportunities -- Chapter 3: Developing the social enterprise concept -- Chapter 4: Social enterprise business plans -- Chapter 5: Measuring social value -- Chapter 6: Earned income -- Chapter 7: Donations and government income -- Chapter 8: Entrpreneurial fundraising and marketing -- Chapter 9: Launch, growth, and goal attainment
Includes bibliographical references and index.
Keywords: SOCIAL ENTREPRENEURSHIP